2021
DOI: 10.3390/en14196043
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Causality between Crude Oil Prices and Exchange Rates: Evidence and Forecasting

Abstract: The relationships between crude oil prices and exchange rates have always been of interest to academics and policy analysts. There are theoretical transmission channels that justify such links; however, the empirical evidence is not clear. Most of the studies on causal relationships in this area have been restricted to a linear framework, which can omit important properties of the investigated dependencies that could be exploited for forecasting purposes. Based on the nonlinear Granger causality tests, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…9 According to the results in Table 3, the real exchange rate neither Granger causes, nor is Granger caused by, the price of oil. The latter of these results supports the finding reported in a recent study by Marquez (2022) while both results support some of the findings reported in a recent study by Orzeszko (2021). Neither of these results is supported by those in a recent study by Przekota and Szczepa ńska-Przekota (2022).…”
Section: Conflicts Of Interestsupporting
confidence: 88%
“…9 According to the results in Table 3, the real exchange rate neither Granger causes, nor is Granger caused by, the price of oil. The latter of these results supports the finding reported in a recent study by Marquez (2022) while both results support some of the findings reported in a recent study by Orzeszko (2021). Neither of these results is supported by those in a recent study by Przekota and Szczepa ńska-Przekota (2022).…”
Section: Conflicts Of Interestsupporting
confidence: 88%
“…In recent years, machine learning algorithms have gained popularity for predictive purposes. They are data-driven, self-adaptive methods requiring very few assumptions about investigated data, which are capable of approximating non-linear relations based on noisy and non-stationary data (Orzeszko, 2021;Fiszeder & Orzeszko, 2021). Among the most popular machine learning algorithms are decision trees and other tree-based methods.…”
Section: Methodsmentioning
confidence: 99%
“…In the studies presented in the literature, the value of a distance measure ε between 0.5 and 1.5 is recommended for consideration (Orzeszko, 2021).…”
Section: Nonlinear Granger Causalitymentioning
confidence: 99%